MedZEB: a new holistic approach for the deep energy retrofitting of residential buildings - Padula, Marco; Picenni, Francesca; Malvezzi, Roberto; Laghi, Luca; Salmeròn Lissén, José Manuel; Sanchez de la Flor, Francisco José; Mateo-Cecilia, Carolina; Soto-Francés, Laura; Assimakopoulos, Maragarita-Niki; Karlessi, Theoni (TECHNE - Journal of Technology for Architecture and Environment, 2018)
The MedZEB (Mediterranean Zero Energy Building) approach aims at stimulating the market uptake of energy deep and beyond retrofitting of existing buildings of the Mediterranean. Its holistic nature implies the evaluation and integration of a range of relevant factors and the effective support to the retrofitting supply chain, also with the help of an ICT platform. Main concern of the approach are residential buildings within a framework dealing with High TRL levels and with already on the market technologies to be combined to create Med-specific cost-optimal Packages of technical Solutions, linked to a Voluntary Certification Scheme. The triggered creation of trust and information exchange will pave the way to new investments and strengthen the Med deep and beyond retrofitting network.